Attitudes of COVID-19 vaccination among college students: A systematic review and meta-analysis of willingness, associated determinants, and reasons for hesitancy. Issue 5 (30th November 2022) - Geng, Hui; Cao, Kexin; Zhang, Jingbing; Wu, Kusheng; Wang, Geng; Liu, Caixia
ABSTRACT: The significance of COVID-19 vaccine has been declared and this study synthesizes the attitudes and determinants in vaccination hesitancy of college students. We searched in PubMed, Web of Science, Cochrane Library and CNKI to enroll the related studies. The modified NOS was used for quality evaluation. Proportion and OR with 95% CI were pooled to estimate the acceptance rates and determinants of COVID-19 vaccination. Data of 34 studies involving 42 countries were pooled. The pooled acceptance rate of COVID-19 vaccination among all the college students was 69% and varies between countries, while medical students have a slightly higher acceptancy rate. Knowledge, trust conception, social behavior, and information sources were important for their decision. Most of the college students intended to COVID-19 vaccination, but the proportion varied among countries. Governments should strengthen credibility, convey trusted information with media influences and improve vaccination services in urging students to be vaccinated.